PENGARUH LATIHAN ACTIVE LOWER ROM TERHADAP RISIKO NEUROPATI PERIFER PADA PENDERITA DIABETES MELLITUS TIPE 2 - Syafitri, Zakia Ulifa; Nurhusna, Nurhusna; Sari, Yulia Indah Permata; Sari, Putri Irwanti; Rudini, Dini (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Diabetes Mellitus (DM) is a long-term metabolic disorder marked by elevated blood sugar levels and can lead to long-term complications, including peripheral neuropathy, which causes decreased foot sensitivity and increases the risk of ulcers and amputation. Preventive efforts can be carried out through physical exercises such as Active Lower Range of Motion, which help improve peripheral blood circulation and nerve sensitivity. This study employed a quasi-experimental approach using a pretest–posttest control group design involving 36 respondents with type 2 DM. The intervention consisted of regular Active Lower ROM exercises, and foot sensitivity was assessed using a 10-gram monofilament. The results showed that most respondents were 60–70 years old and predominantly female. Wilcoxon and Mann-Whitney analyses indicated a notable change was observed between the pre-intervention and post-intervention results (p=0.000), demonstrating that ALROM exercises effectively reduce the risk of peripheral neuropathy. This exercise can serve as a safe, simple, and beneficial non-pharmacological therapy for individuals with type 2 DM.